Biodegradation rate of Esso oil (Tapis A) and growth on some selected hydrocarbons by bacteria isolated from Port Dickson coastal waters - Ivy Wong Ling Ling (Universiti Pertanian Malaysia, 2012)
Two bacteria isolated from Port Dickson coastal waters were identified and their petroleum degrading activities were determined.